Confinamiento y su incidencia en las relaciones familiares de la ciudadela San José de la parroquia 12 de marzo del cantón Portoviejo - Macías Moreira, Xavier Alexis (2021)
Families have lived a series of changes and adaptations during confinement by the COVID-19 pandemic, so the objective of this study was analyze the confinement and its influence on families from Ciudadela “San José”- Parroquia 12 de marzo- Canton Portoviejo. The development of this research was based on a descriptive study, with a quantitative focus, to obtain relevant information on the topic study. It used a bibliographic review with an empirical level, the survey technique was made and 10-questions was used as an instrument. The sample was random with a total of 30 families from “San José” citadel. The results showed the reality in which the families are situated of how it impacted each member of the household and the changes they have had to make during confinement due to the COVID-19 pandemic in order to adapt to this new reality, in conclusion, The family system faced certain adversities and social problems that affected and influenced the coexistence with its members, in some cases it was positive, because modifications were made to adjust to the context in which the families lived, strengthening ties by improving their family relationships, in others, the confinement caused instability in the coexistence, due to the fact that problems arose to overcome the calamities that existed in their environment.